WORKING OUT QUALITY STANDARDS OF MODEL COMPOSITION SAMPLES OF GRANULATED DOSAGE FORM WITH GLUTATHIONE RESTORED - K. A. Alekseeva; D. I. Pisarev; A. Yu. Malyutina; E. T. Zhilyakova; Z. E. Tsvetkova; Yu. A. Polkovnikova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2019)
Biologically active sulfur-containing compounds (BASC) exhibit pronounced antioxidant properties. Glutathione reduced (GSH) occupies a particular position among these compounds. It represents a key link in the 3 antioxidant systems of the body from the existing four. Based on the foregoing, a GSH-based dosage form with antioxidant properties was proposed. The aim of this study is to work out a model granulated dosage form based on GSH and methods of its analysis by means of pre-column derivatization with ortho-phthalic aldehyde.Materials and methods. GSH and granulated dosage form based on GSH obtained by wet granulation were used as the object of the study. Quantitative evaluation of GSH content in the obtained granules was carried out using pre-column derivatization by the method of reversed-phase high-performance chromatography (RP HPLC). Ortho-phthalic aldehyde was used as a derivatizing agent. A diode-array detector was used to detect the resulting derivative. Ortho-phthalic aldehyde was used as a derivatizing agent. A diode-matrix detector was used to find out the resulting derivative.Results. In the course of the work, a model dosage form was created - granules based on GSH. By reference to the recommendations on the dosage of the drug, the concentration of the active substance was selected. Lactose was chosen as an auxiliary component. Physical and technological characteristics of a model sample of granules with GSH and lactose as a filler were studied. A method of quantitative determination of GSH in granules using pre-column derivatization with ortho-phthalic aldehyde was developed and validated by HPLC. The method of quantitative determination of GSH in granules with the use of pre-column derivatization by ortho-phthalic aldehyde by HPLC was developed and validated.Conclusion. The developed granulated dosage form meets the requirements given in the pharmacopoeial item "Granules" according to the analyzed indicators. Using the validation evaluation it was established, that the developed methods for the quantitative determination of GSH in granules is correct, precise and specific.